Kehamilan dengan miastenia gravis: laporan kasus - Anthonyus Gracius Bima Pakasi; Made Bagus Dwi Aryana; Anna Marita Gelgel (DiscoverSys Inc., 2020)
Introduction: Myasthenia gravis (MG) is an autoimmune disorder of neuromuscular transmission characterized by weakness of the skeletal muscles. Pregnancy with myasthenia gravis must have particular concern because of changes in body physiology and potential myastenic attack which can be dangerous if it is not recognized quickly and received adequate treatment. The aim of this case report is to provide an overview of the treatment of pregnancies with myasthenia gravis.Case: A case report of a 32 year old woman who came with complaints of dyspnoea, and was known to have a history of myasthenia gravis that had been experienced for seven years and received pyridostigmine therapy 4x60 mg orally. Severe tightness was accompanied by coughing and caused the saturation to fall below 95%, and it was decided to give intravenous neostigmine, and the tightness dramatically improved. Ultrasound evaluation of pregnancy showed, gestational age 33 weeks and estimated fetal weight 2525 grams and decided for monitoring and conservative therapy and administration of 12 grams of dexamethasone intra-muscular for maturation of fetal lungs. At 36 weeks of gestation the patient came back because of vaginal discharge and an examination was carried out so that non-reactive non-stress test results were found and it was decided to do a caesarian section immediately, until finally a baby boy weighing 3000 grams APGAR 8-9 was born, without any abnormalities. The mother was discharged in good condition and was still receiving pyridostigmine 4x60 mg orally.Conclusion: Myasthenia gravis in pregnancy is something that is rarely found, but it requires special attention to mothers and babies because it can cause mortality if not handled properly. Precautions and proper handling during myastenic attacks will give a better clinical outcome. Pendahuluan: Miastenia gravis (MG) adalah gangguan autoimun dari transmisi neuromuskuler yang ditandai dengan kelemahan otot skeletal. Kehamilan dengan miastenia gravis menjadi perhatian khusus oleh karena perubahan fisiologi tubuh dan adanya ancaman serangan miastenik yang dapat membahayakan apabila tidak diketahui secara cepat dan mendapatkan penanganan yang adekuat. Tujuan dari laporan kasus ini adalah memberikan gambaran penangnan terhadap kehamilan dengan miastenia gravis.Kasus: Laporan kasus perempuan usia 32 tahun yang datang dengan keluhan sesak, dan diketahui memiliki riwayat miastenia gravis yang sudah dialami semenjak tujug tahun dan mendapat terapi piridostigmin 4x60 mg per oral. Sesak yang berat disertai dengan batuk dan menyababkan saturasi turun hingga dibawah 95%, dan diputuskan untuk memberikan neostigmine intravena, dan secara dramatis sesak membaik. Evaluasi ultrasonografi kehamilan menunjukkan, usia kehamilan 33 minggu dan tafsiran berat janin 2525 gram dan diputuskan untuk monitoring dan terapi konservatif dan pemberian deksamethason 12 gram intra muskular untuk pematangan paru janin. Pada usia kehamilan 36 minggu pasien kembali datang oleh karena keluar air pervaginam dan dilakukan pemeriksaan sehingga ditemukan hasil non stress test non reaktif dan diputuskan untuk melakukan tindakan caesarian section segera, hingga akhirnya lahir bayi laki-laki berat 3000 gram APGAR 8-9, tanpa kelainan kongenital. Kondisi ibu dipulangkan dengan keadaan baik dan tetap mendapat terapi piridostigmin 4x60 mg per oral.Simpulan: Miastenia gravis pada kehamilan merupakan suatu hal yang jarang ditemukan, namun memerlukan perhatian khusus pada ibu juga pada bayi karena dapat menimbulkan mortalitas bila tidak tertangani dengan baik. Kewaspadaan dan penanganan yang tepat saat serangan miastenik akan meberikan luaran klinis yang lebih baik.